Improving the Flux-Weakening Capability of Interior Permanent Magnet Machines by Number of Turns Changing Methodology - Gündoğdu, Tayfun (Fırat University, 2022)
In this paper, an interior permanent magnet (IPM) machine having two sets of windings with different number of turns is developed to improve the limited flux-weakening (FW) capability and efficiency, simultaneously. The flux-adjustable range appears to be somewhat limited because of the limited maximum inverter voltage and high magnetic saturation, which degrades the FW capability. To address its restricted FW capability, a unique winding-switching concept is introduced, in which auxiliary coils with lower turns alternately function as the secondary armature winding, resulting in flux-linkage reduction within the same phase. Winding topologies, design considerations, the FW principle, and FW computations have all been addressed. To validate the feasibility of the proposed FW enhancement strategy, a co-simulation procedure based on the 2D finite element method (FEM) and MatLab codes is used to determine the steady-state and FW performance characteristics of IPM machines with various winding topologies. All steady-state and FW performance characteristics of the conventional IPM machine and the proposed IPM machines have been compared quantitatively. Furthermore, to ensure the accuracy of the analytical and numerical calculations provided in this study, the predicted efficiency map of the original Toyota Prius 2010 IPM machine is validated using the efficiency measurements provided.
Keywords: Engineering; Mühendislik